USM THE FIRST MALAYSIAN UNIVERSITY RECOGNISED BY IFT CHICAGO - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 19 January 2016 – The Food Technology undergraduate programme offered by the School of Industrial Technology at Universiti Sains Malaysia (USM) since 1972, has been given recognition by the Institute of Food Technologists Chicago (IFT) in the United States of America (USA) and now provides scholarship opportunities for its students to pursue their studies there.